Penanaman Nilai Demokrasi dan Toleransi Melalui Pendidikan Kewarganegaraan di MI/SD - Sabariah, Sabariah; Gofur, Abdul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Civic Education (PKn) plays an important role in shaping students' character, especially in instilling democratic values ​​and tolerance from an early age. At the Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels, PKn teaching aims to equip students with an understanding of the rights and obligations of citizens and the importance of respecting differences. This study aims to analyze how civic education can instill democratic values ​​and tolerance in MI/SD students. The method used is library research, which examines various literature related to the implementation of civic education. The results of the study indicate that PKn learning can be implemented well through a discussion-based approach, group work, and simulation of democratic life, which helps students to understand these principles directly. However, the implementation of this education faces several challenges, such as limited supporting facilities and unequal understanding among educators.